Single Parents - Andrzej Klimczuk (Encyclopedia of Human Services and Diversity, 2014)
Services for single parents constitute a category of child and family services. These services are carried out by public and non-governmental bodies for people who are single parents by the unfortunate events or by their own choice. Individuals come to single parenthood mainly through divorce, separation, birth outside of marriage, child abuse/neglect, death of a partner/widowhood, and adoption.
Keywords: H75; I38; J18; 300; Single Parents; social services